MEMBANGUN KINERJA MELALUI LINGKUNGAN KONDUSIF, PEMBERIAN MOTIVASI DAN PROPORSIONAL BEBAN KERJA - Chotamul Fajri; Yasir Terza Rahman; Wahyudi Wahyudi (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
As a company engaged in the food sector, providing satisfaction to customers is an obligation, and one of them is through improving employee performance. That is, the company encourages all employees to work professionally and with integrity, in this case, be able to serve food with good taste, provide friendly, responsive, and fast service. This study aims, to reveal the factors that significantly affect the performance of Holland Bakery employees in Depok City. Furthermore, to prove these objectives, a scientific approach was carried out, namely using quantitative methods and regression analysis. In the operationalization of the research, data collection was carried out by distributing questionnaires to 84 respondents, using a simple random technique. Based on regression analysis, it is known that the work pattern at Holland Bakery is more influenced by the work environment. This means that the work environment has a dominant role in productivity and morale. This suggests the importance of building harmonious interaction and communication between employees, so that a solid work team is built. However, companies need to take into account the workload aspect. As the results of statistical analysis, workload shows a role that allows employee performance to decline.